Islamic Boarding Schools’ Educational Response to Roblox Addiction Among Qur’an-Memorizing Students - Muhammad Ilham Halwani; Fihris Fihris; Luthfiyah Luthfiyah; Bakti Fatwa Anbiya; Nasikhin Nasikhin (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat (LP3M) IAI Al Urwatul Wutsqo - Jombang, 2025)
This study aims to analyze the negative impact of Roblox games on students who memorize the Qur'an and the preventive measures implemented at Al Masthuriyah Islamic Boarding School. Using a qualitative case study design and data analysis based on the Miles and Huberman model, this study identifies three levels of Roblox playing intensity: low, moderate, and high. Students with low intensity play for 30 minutes to 1 hour, 1–2 times a week, as entertainment after memorization, with Islamic content options. The moderate group plays for 1–2 hours, 3–4 times a week, for online relaxation and socialization, while maintaining a balance between worship and academics. Meanwhile, the high group plays 2–4 hours or more almost every day, disrupting memorization time, congregational prayers, and sleep. Negative impacts include decreased memorization recall due to excessive stimulation, time management issues, and exposure to content contrary to Islamic values, such as inappropriate avatars, magic, or immoral interactions. The boarding school responded with a comprehensive strategy: gadget regulations based on age and memorization performance, access restrictions limited to Saturdays and Sundays from 3:00 PM to 5:00 PM, support for teachers, and digital literacy based on Islamic values. Students are taught the dangers of addiction from a Sharia perspective, such as wastefulness and negligence. These findings provide a technology management model that can be replicated by Islamic boarding schools.